2012
DOI: 10.1371/journal.pone.0041076
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Changes in Cardiac Myofilament Function following the Acute Activation of Estrogen Receptor-Alpha

Abstract: Estrogens have well-recognized and complex cardiovascular effects, including altering myocardial contractility through changes in myofilament function. The presence of multiple estrogen receptor (ER) isoforms in the heart may explain some discrepant findings about the cardiac effects of estrogens. Most studies examining the impact of estrogens on the heart have focused on chronic changes in estrogen levels, and have not investigated rapid, non-genomic pathways. The first objective of this study was to determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 32 publications
(43 reference statements)
2
15
0
Order By: Relevance
“…Time to peak and times from peak to 25%, 50% and 75% Ca 2+ transient decay were dose-dependently increased (Figure 5H and Table S3), reflecting sarcomere length measurements. A potential mechanism for slow Ca 2+ transient decay is acute ER signaling through PKA to alter the phosphorylation status of cTnI [27,29,33]. To test this, cardiac myocytes were treated with Ral +/- isoproterenol to determine whether Ral causes dephosphorylation of cTnI.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Time to peak and times from peak to 25%, 50% and 75% Ca 2+ transient decay were dose-dependently increased (Figure 5H and Table S3), reflecting sarcomere length measurements. A potential mechanism for slow Ca 2+ transient decay is acute ER signaling through PKA to alter the phosphorylation status of cTnI [27,29,33]. To test this, cardiac myocytes were treated with Ral +/- isoproterenol to determine whether Ral causes dephosphorylation of cTnI.…”
Section: Resultsmentioning
confidence: 99%
“…Acute, non-genomic effects of Tam administration have thus far not been considered as a contributor to Tam-induced dilated cardiomyopathy in Tg(αMHC-MerCreMer) mice. PKA is implicated as a non-genomic signaling target of ERs with 17β-estradiol, causing decreased phosphorylation of PKA target proteins with subsequent alterations in contraction and SR Ca 2+ release and reuptake [2729]. It is currently unknown whether acute ER signaling through Tam has direct effects on cardiac myocyte function.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in mice, the effects of estrogens mediated by ERα can improve vascular function and reduce atherosclerosis [110]. Some studies also showed that estrogen can prevent cardiac fibrosis by blocking the fibroblast to myofibroblast transition via interactions with ERβ [111].…”
Section: Estrogen and Ers In Age–related Diseasesmentioning
confidence: 99%
“…Acute application of high concentrations (10 to 30 μM) of 17β-estradiol also reduces the amplitudes of Ca 2+ transients and contractions in isolated ventricular myocytes [57, 110]. Interestingly, stimulation of oestrogen receptor α with PPT (4,49,499-(4-propyl-[1 H ]-pyrazole-1,3,5-triyl) trisphenol; 100 nM) has been shown to decrease myofilament Ca 2+ sensitivity [64]. There is also evidence that oestrogen can acutely modify electrophysiological properties of the heart.…”
Section: The Impact Of Sex Steroid Hormones On Cardiac Ec Coupling Mementioning
confidence: 99%